Effect of polyacrylate polymer on the mechanical and water retention properties of cemented soil: A multiscale investigation - Lei Wang; Yongsheng Yao; Jue Li (Case Studies in Construction Materials)
Granitic residual soils (GRS) occupy substantial deposits in many regions but exhibit deficiencies restricting direct engineering applications. This study investigated polyacrylate (PA) polymer treatment to enhance the mechanical and hydrological properties of GRS. Triaxial tests evaluated the effects of PA content (0–3 %) on shear strength parameters under varied confining pressures. Soil-water retention characteristics were determined using pressure plate and filter paper methods. Microstructural analyses via scanning electron microscopy and pore attribute quantification furnished insights. Results showed PA increased peak deviator stress and cohesion in a content-sensitive manner up to an optimum 2 % dosage. A modified Duncan-Chang model accurately described the nonlinear stress-strain behavior. PA amplified water retention across the entire suction domain by elevating the air entry value attributed to microstructural changes. Morphological analyses indicated PA formed binding membranes consolidating particles with redistributed pore attributes towards stabler, load-resisting configurations. Quantitative links validated hypothesized mechanisms whereby optimized pore architectures directly translated bulk fabric cohesion and friction enhancement. Multi-scale evidence synthesized a self-consistent microscopic mechanism of PA-mediated pore network reconstitution systematically strengthening the granular framework. This study demonstrated polyacrylate modification optimizes key engineering properties of naturally deficient GRS, offering design guidance for sustainable geotechnical applications exploiting abundant residual soil resources.